Reliving the Past: Yoking Myth and History in ShashiTharoor's The Great Indian Novel - V G, Prasanth (International Journal of Psychosocial Rehabilitation, 2020)
Tharoorhas made his debut in the literary scenario of Indian English fiction with the allegorical novel, titledThe Great Indian Novelthat attempts to transport the past of the epic days with its plurality of characters and events to the post independent India by subtly establishing a simulacrum between the characters and events of the past and the present. The greatest among all works of literature in size and intensity, Mahabharata still stands as a great reservoir for number of writers to draw inspiration from and to interpret according to the contemporaneity. Number of attempts has been made in different Indian languages as well as in foreign languages by writers of eminence to adapt stories from Mahabharatain order to surface their diverse perspectives and interpretations. It is quite obvious that Tharoor has found a good vehicle in Mahabharata, which can claim to include everything under the sun in its gamut, to make “an attempt to retell the political history of twentieth century India, through a fictional recasting of its events, episodes and characters” (Bookless 15). This paper attempts to establish how the characters of the epic are made to relive in the twentieth century India whereby an allegorical reading of the Mahabharata is brought into, with great precision and alacrity.